Terapia ocupacional para actividades cotidianas significativas en adultos mayores del proyecto envejeciendo juntos del GAD Marcabelí, provincia de El Oro, periodo 2022 - Jumbo Sánchez, Jahneth Priscila (2022)
2.1. Abstract The present investigation was carried out with the objective of determining how Occupational Therapy influences the improvement of the significant daily activities of the older adults of the project aging together of the GAD Marcabelí, province of El Oro, period 2022. For this, a design of non-experimental cross-sectional field study, descriptive, explanatory and purposeful, with a mixed approach, using the methods: Scientific, Descriptive, Analytical and Hermeneutical in a population sample of 20 older adults aged 73 years. Instruments such as: the survey and the Barthel Index were applied, from which it was obtained as a result that most older adults have a high degree of autonomy in certain significant daily activities such as feeding, dressing / undressing, bathing, climbing and go down stairs; given that the implementation of occupational therapy activities contributes to the older adult carrying out these activities by himself or with the least possible number of supports. For this reason, it is considered important to make use of the alternative proposal presented in this thesis report, with the purpose of achieving maximum independence and personal motivation, that is, improving their skills, increasing their self-esteem, their sense of responsibility and participation in your daily tasks. Keywords: occupational therapy, older adults, daily activities, independence